CXCL13, CXCL10 and CXCL8 as Indicators of Ocular and Neurological Involvement in Patients With Ocular Syphilis: An Observational Descriptive Study - van der Merwe, Laurie W.; Snyders, Candice; Kidd, Martin; Chegou, Novel N.; Walzl, Gerhard; Smit, Derrick P. (Frontiers in Ophthalmology, 2022)
Abstract Aim: To investigate the role of the chemokines CXCL13, CXCL10 and CXCL8 in the diagnosis of ocular- and neurosyphilis by examining the serum, aqueous humour (AH) and cerebrospinal fluid (CSF) of patients with ocular syphilis. Methods: An observational descriptive study was performed prospectively at Tygerberg Academic Hospital in Cape Town, South Africa from 1 February 2018 till 31 January 2021 which enrolled 23 participants. 14 Patients were male and 9 female, 15 patients were HIV positive, and all patients were newly diagnosed with ocular syphilis. Upon diagnosis of ocular syphilis, the HIV status of each patient was determined, and 3 samples (AH, serum and CSF) were collected to measure the levels of CXCL13, CXCL10 and CXCL8 in each. All patients were treated with 14 days of intravenous Penicillin G and topical corticosteroid drops for uveitis. Results: The mean concentrations of all 3 biomarkers were higher in the AH and CSF than in the serum. The mean concentrations of the 3 measured biomarkers were markedly different when comparing both AH and CSF levels to serum levels. The level of CXCL13 measured in the AH correlated well with the concentrations found in the CSF of patients with neurosyphilis. In patients with neurosyphilis, mean AH levels of CXCL13 and CXCL10 were markedly higher than in serum while mean CSF levels of CXCL10 were also markedly higher than in serum. Also, the AH/serum ratio of CXCL13 and CXCL10, as well as the CSF/serum ratio of CXCL10, was much higher in patients with neurosyphilis than without. In patients with HIV infection, mean AH CXCL13 levels were much higher than in patients without HIV infection. Conclusion: The levels of CXCL13, CXCL10 and CXCL8 in the AH of patients with neurosyphilis are similar to previously reported levels in the CSF of patients with neurosyphilis and can potentially be an adjunct in the diagnosis of ocular syphilis. Patients with ocular syphilis who tested negative for neurosyphilis with conventional CSF testing showed features of neurosyphilis when analysing the CSF chemokines.